An NOS3 Haplotype Is Protective against Hypertension in a Caucasian Population - Georgios D. Kitsios; Elias Zintzaras (International Journal of Hypertension)
The endothelial nitric oxide synthase gene (NOS3) has been implicated in the development of hypertension, although the specific role of variants and haplotypes has not been clarified. In this study, the association of three polymorphisms (promoter T786C, intronic 4a/b, and nonsynonymous G894T) was tested in a case-control sample of 230 patients with essential hypertension and 306 healthy controls. Haplotype analysis was also performed. The mutant allele a∗ of the 4a/b polymorphism showed a protective effect against hypertension under a dominant model (odds ratio=0.64, 95% confidence interval (0.44–0.93)), although this effect was not significant after the adjustment for covariates (𝑃=0.06). The estimated frequency of the haplotype composed of the T786∗, 4a∗, and G894∗ alleles was significantly higher in controls (5.5%) compared to cases (2%). These results indicate that although individual NOS3 polymorphisms are not associated with hypertension, a rare haplotype of the gene might be protective against the development of hypertension.